In situ DART‐MS as a Versatile and Rapid Dereplication Tool in Lichenology: Chemical Fingerprinting of Ophioparma ventosa. Issue 6 (30th September 2016) - Le Pogam, Pierre; Le Lamer, Anne‐Cécile; Legouin, Béatrice; Boustie, Joël; Rondeau, David
Abstract: Introduction: Lichens widely occur all over the world and are known to produce unique secondary metabolites with various biological activities. Objective: To develop high‐throughput screening approaches requiring little to no sample preparation to alleviate the dereplication holdup and accelerate the discovery workflow of new structures from lichens. Methodology: The extracellular distribution of lichen metabolites is incentive for in situ chemical profiling of lichens using the ambient mass spectrometry DART‐MS. For this purpose, the chlorolichen Ophioparma ventosa, producing an array of lichen polyphenolics that encompass the main structural classes associated to lichen chemodiversity, represented a relevant model to assess the versatility of this platform. The feasibility of this approach was first established by analysing the pure compounds known from this species prior to being extended to different solid organs of the lichen. Results: All tested compounds could be detected in positive and negative ion modes, most often with prevalent protonated or deprotonated molecules. Only depsides underwent a significant in‐source fragmentation in both ionisation modes, which should be regarded as an added value for their structural elucidation. In situ DART‐MS analyses of Ophioparma ventosa provided an extensive chemical profile and noteworthy pinpointed miriquidic acid, an unusual lichen depside so far unknown within this species. At last, in situ DART‐MS granted a first insight into the distribution of the metabolites within the lichen. Conclusion: DART‐MS represents a versatile tool to the wide field of lichenology, facilitating accelerated and sharp analyses of lichens and bypassing costly and tedious procedures of solvent extraction. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The extracellular distribution of lichen metabolites is incentive for their in situ chemical profiling. Through the specific example of Ophioparma ventosa, the present work emphasizes the potential of DART‐MS to facilitate complete chemical fingerprints from unprocessed pieces of lichen. The dereplicative interest of this method is demonstrated through the detection of miriquidic acid, a rare depside so far unknown from O. ventosa . Interestingly, DART‐MS also provided a first insight into the distribution of the secondary metabolites within this lichen.